Scent of death: Emission and behavioral role of 1-nonene in entomopathogenic nematode Steinernema kraussei - Rasa Čepulytė; Evelina Osinska; Violeta Apšegaitė; Deimantė Tiškevičiūtė; Vincas Būda (PLoS ONE, 2025)
Entomopathogenic nematodes (EPNs) provide a natural alternative to synthetic pesticides for pest control. Understanding how EPNs respond to volatile cues including those released by infected cadavers is crucial for determining the behavior control necessary for improving their effectiveness. In this study, we tested the response of Steinernema kraussei, a cruiser foraging species, to 1-nonene. Additionally, we analyzed the emission dynamics of this compound from Galleria mellonella larvae infected by three different EPN species: S. kraussei, S. carpocapsae, and S. feltiae. Concentrations of 1-nonene at 20 mM and above elicited a repellent behavior in S. kraussei. Ethanol, used as a solvent for 1-nonene, was attractive to this EPN at high concentrations only. The emission of 1-nonene was the lowest from larvae infected by S. feltiae compared to those infected by the other two species. Larvae infected with S. kraussei released 15 times more 1-nonene than those infected with S. feltiae, while larvae infected with S. carpocapsae released 76 times more than those infected with S. feltiae and 5 times more than those infected with S. kraussei. Comparing our findings to previous research behavioral responses to environmental compounds (ethanol and 1-nonene) suggest that EPNs with cruiser (S. kraussei) and intermediate (S. feltiae) foraging strategies show similar responses, distinct from those of ambusher’s (S. carpocapsae).